The Association of Orthostatic Hypotension With Ambulatory Blood Pressure Phenotypes in SPRINT. (22nd May 2021) - Ghazi, Lama; Drawz, Paul E; Pajewski, Nicholas M; Juraschek, Stephen P
Abstract: Background: Clinic blood pressure (BP) when measured in the seated position, can miss meaningful BP phenotypes, including low ambulatory BP (white coat effects [WCE]) or high supine BP (nocturnal non-dipping). Orthostatic hypotension (OH) measured using both seated (or supine) and standing BP, could identify phenotypes poorly captured by seated clinic BP alone. Methods: We examined the association of OH with WCE and night-to-daytime systolic BP (SBP) in a subpopulation of SPRINT, a randomized trial testing the effects of intensive or standard (<120 vs. <140 mm Hg) SBP treatment strategies in adults at increased risk of cardiovascular disease. OH was assessed during follow-up (6, 12, and 24 months) and defined as a decrease in mean seated SBP ≥20 or diastolic BP ≥10 mm Hg after 1 min of standing. WCE, based on 24-hour ambulatory BP monitoring performed at 27 months, was defined as the difference between 27-month seated clinic and daytime ambulatory BP ≥20/≥10 mm Hg. Reverse dipping was defined as a ratio of night-to-daytime SBP >1. Results: Of 897 adults (mean age 71.5±9.5 years, 29% female, 28% black), 128 had OH at least once. Among those with OH, 15% had WCE (vs. 7% without OH). Moreover, 25% of those with OH demonstrated a non-dipping pattern (vs. 14% without OH). OH was positively associated with both WCE (OR=2.24; 95%CI: 1.28, 4.27) and reverse dipping (OR=2.29; 95% CI: 1.31, 3.99). Conclusions: The identification of OH in clinic was associated with two BP phenotypes often missed with traditional seated BP assessments. Further studies on mechanisms of these relationships are needed. Clinical trials registration: Trial Number NCT03569020. Graphical Abstract: